Development of standard volume equations for Malaysian timber trees I: Dark Red and Light Red Merantis - Wan Mohd, Wan Razali (Universiti Putra Malaysia Press, 2013)
Volume is important in updating and projecting inventories, determining harvest level or allowable cut, scheduling the harvest unit for logging, analyzing potential alternatives stand treatments and determining site-productivity. Inherent in the preparation of a forest management plan, an annual forest working plan and a forest harvesting plan is the availability of a volume table, which is usually derived from a functional relationship using a diameter and/or a log length or tree height. Four unweighted and five weighted volume equations were fitted by the method of least squares to volume data of each of the two species groups of Dipterocarp Merantis - Dark Red Meranti (DRM) and Light Red Meranti (LRM) obtained from the mixed tropical forest of Malaysia. Furnival`s Index (FI) was used as the criterion for selecting the best fit regression equation of each species group under study. The equation weighted by 1/D2H showed its superiority over other equations in both species groups.